Pattern of sexually transmitted infections in a tertiary care centre at Puducherry - Devi S; Vetrichevvel T; Pise Gajanan; Thappa Devinder (Wolters Kluwer Medknow Publications, 2009)
Background: The prevalence of sexually transmitted infections (STI) varies widely from region to region in our country. Aims: To highlight the pattern of STIs and the profile of patients with HIV infection in STD patients as seen at our hospital. Methods: A retrospective chart analysis of clients attending STI clinic, JIPMER, Puducherry, from June 2004 to June 2006 was done. Results: A total of 866 clients attended our STI clinic, out of whom 435 (50.2%) had proven STI. STIs were more common in men, with a male (290): female (145) ratio of 2:1. Their age ranged from 1 year to 75 years (mean age = 32.38 years) with the maximum number of patients in the age group of 21-30 years, while children constituted only 2.8%. Herpes genitalis (107 patients, 32.8%) was the most common ulcerative STI, while genital wart was the most common nonulcerative STI (56 patients, 17.1%). Non-gonococcal urethritis (46 patients, 14.1%) was more common than gonococcal urethritis. HIV infection was the most common STI in our study, at an alarmingly high rate of 34.5% (151/435). HIV seropositivity was more common in patients who presented with ulcerative STIs than with nonulcerative STIs. Conclusions: Herpes genitalis was the most common ulcerative STD, while genital wart was the most common nonulcerative STI in our study. The prevalence of HIV among STI clients in India has been on the rise, but has quite alarmingly become the most common STI in our study.